Performance analysis of masonry building with courtyard - Shrestha, R.; Prajapati, R.S. (Journal of Science and Engineering, 2015)
A courtyard masonry building is a series of masonry buildings built in-close forming a square or rectangular space at middle of buildings. Courtyard is the central part of the buildings. It is also the flourishing place for social and cultural activities and the safer place for rescue and shelter during earthquake. In different places of Kathmandu valley courtyard typed housing is found which are historically important and preserved as a world heritage sites. These buildings are susceptible to damage due to interaction of adjacent building and due to the arrangement of buildings in courtyard pattern. This study evaluates the performance of the buildings in court-yard form during seismic loading. Typical arrangement and height of the buildings in conglomeration which is usually found in different parts of Bhaktapur district are selected. From the simulation and analysis, the buildings in conglomeration are more flexible and resist more seismic force, while the buildings in corner are more vulnerable, and hence weak for the same seismic loading.